2021
DOI: 10.20524/aog.2021.0653
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and capsule endoscopy: automatic detection of vascular lesions using a convolutional neural network

Abstract: Background Capsule endoscopy (CE) is the first line for evaluation of patients with obscure gastrointestinal bleeding. A wide range of small intestinal vascular lesions with different hemorrhagic potential are frequently found in these patients. Nevertheless, reading CE exams is time-consuming and prone to errors. Convolutional neural networks (CNN) are artificial intelligence tools with high performance levels in image analysis. This study aimed to develop a CNN-based model for identification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, most studies focus on the development of deep learning models in automatic identification of a specific type of lesion in either the small bowel or the colon. In the small bowel, there are very accurate deep learning models capable of detecting different types of vascular lesions, as well as predicting their bleeding risk accuracy 14 . In the colon, although the vast majority of retrospective studies focus on the detection of protruding lesions, there are already published AI algorithms not only for automatic detection of blood or hematic residues 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most studies focus on the development of deep learning models in automatic identification of a specific type of lesion in either the small bowel or the colon. In the small bowel, there are very accurate deep learning models capable of detecting different types of vascular lesions, as well as predicting their bleeding risk accuracy 14 . In the colon, although the vast majority of retrospective studies focus on the detection of protruding lesions, there are already published AI algorithms not only for automatic detection of blood or hematic residues 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Many articles have been published using this type of artificial intelligence (AI) system in different image-base procedures, including CE. Currently, there is published research in the field of automatic detection of vascular lesions during CE, in the small bowel, which has high overall accuracy 11 12 13 14 15 . These algorithms can not only identify different types of vascular lesions (red spots, angiectasia and/or varices), but also predict their likelihood of bleeding, according to Saurin classification 14 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Ribeiro et al developed an AI algorithm for detecting blood in CCE images. 29 They retrospectively extracted greater than 5,000 CCE pictures used to train and validate the CNN, achieving a sensitivity of 99.8% and specificity of 93.2% for the detection of blood. In another study, the same authors found a deep learning algorithm capable of detecting protruding lesions in CCE images with a sensitivity of 90.7% and specificity of 92.6%.…”
Section: Definitionsmentioning
confidence: 99%
“…This study aimed to develop and test a Convolutional Neural Network (CNN)-based model for panendoscopic automatic detection of vascular lesions during CE. 1 2 3 4 5 6 7 8 9…”
mentioning
confidence: 99%